Epidemiological analysis of 2,368 pesticide poisoning patients in Quzhou City, China - Zheng, Xiawen; Zheng, Ting; Wang, Lushan; Jiao, Shiling; Jiang, Xianchen; Lai, Shiming; Zhan, Bingdong (Frontiers in Public Health, 2025)
IntroductionPesticides, which are chemical compounds, are mainly utilized to eradicate pests such as insects, rodents, fungi, and unwanted plants (weeds). However, improper application or storage of pesticides can lead to poisoning incidents. In China, many patients tend to abandon treatment and return home when their condition severely deteriorates. This behavior makes it challenging for medical institutions to precisely track the patients’ subsequent conditions, resulting in the reported number of deaths in the system being lower than the actual figure.MethodsThis research obtained case data on pesticide poisoning in Quzhou city from 2015 to 2022 (2,368 confirmed cases) from ODSRS, using patient ID card numbers on the report cards to match cause-of-death data in the Zhejiang Chronic Disease Monitoring Information Management System. Excel 2013 was used for database establishment, Graph Prism 9.5.0 for statistical analysis and graphing, and ArcMAP10.2 for creating regional distribution maps. The chi-square test compared categorical variable groups; binary logistic regression explored factors influencing pesticide poisoning mortality.ResultsFrom 2015 to 2022, a total of 2,368 pesticide poisoning cases were documented in Quzhou City, exhibiting a downward trend. Among them, 280 patients died, with a case-fatality rate of 11.82%. The fatality rate was higher in males (13.35%) compared to females (10.03%), and it increased with age. Insecticides were implicated in 66.05% of the poisoning cases, followed by herbicides (20.82%) and rodenticides (9.71%). Notably, herbicides had the highest fatality rate at 15.21%. Non-occupational poisoning accounted for 91.01% of the cases, with suicidal poisoning constituting 65.57% and having a fatality rate of 15.07%. Statistically significant differences were observed in the distributions of fatalities across different genders, age groups, pesticide types, and causes of poisoning (p < 0.05). Pesticide poisoning was reported in all six counties of Quzhou City, with Kaihua County having the highest incidence, mortality, and case-fatality rate.ConclusionThis study indicates that the actual fatality rate of pesticide poisoning patients is substantially higher than the reported rate. Additionally, being male, over 40 years old, and having non-occupational exposure to herbicides were associated with higher death odds ratios.